2014
DOI: 10.1371/journal.pone.0095603
|View full text |Cite
|
Sign up to set email alerts
|

National Profile and Treatment Outcomes of Patients with Extrapulmonary Tuberculosis in Bénin

Abstract: BackgroundIn sub-Saharan Africa, there is a dearth of published literature on extrapulmonary tuberculosis (EPTB).ObjectiveTo describe demographic, diagnostic and HIV-status characteristics of patients with EPTB in Bénin, their treatment outcomes, and among those who completed their treatment in the Centre National Hospitalier de Pneumo-Phtisiologie (CNHP-P), the proportion whose bodyweight increased during treatment.Material and FindingsThis was a retrospective cohort study with comparisons made between EPTB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
42
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 20 publications
(18 reference statements)
20
42
2
Order By: Relevance
“…Majority, at 22.3% and 30% of TB patients were in the age groups of 15-24 and 25-34 years respectively. This report is also in line with other literatures 5,10,[14][15] which indicated that, TB mainly affects the reproductive segment of the population. This might be due to high HIV prevalence in these age groups (personal opinion).…”
Section: Discussionsupporting
confidence: 93%
“…Majority, at 22.3% and 30% of TB patients were in the age groups of 15-24 and 25-34 years respectively. This report is also in line with other literatures 5,10,[14][15] which indicated that, TB mainly affects the reproductive segment of the population. This might be due to high HIV prevalence in these age groups (personal opinion).…”
Section: Discussionsupporting
confidence: 93%
“…The higher success rate in HIV-positive patients are not consistent with what is usually observed in the TB drug susceptible population, where success rates are lower among HIV-positive due to higher death rate [15]. We also report a high case fatality rate among HIV-positive patients for both MDR and PDR-TB patients, likely to be attributable to HIV as already shown in previous studies [16][17][18]. Despite the higher proportion of rifampicin resistant PDR-TB among HIV-positive patients, the failure rate of PDR-TB treatment was similar between HIV-positive and negative patients.…”
Section: Discussioncontrasting
confidence: 63%
“…With the occurrence of Human Immunodeficiency Virus (HIV) infection, TB is increasing either in developing than developed countries. ExtraPulmonary Tuberculosis (EPTB) characterized by the development of TB outside the lungs is also increasing in term of frequency worldwide [1][2][3][4][5][6][7][8]. However, clinical presentations are various and delaying the diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The other factor could be physician-based because of absence or delay in the screening of TB among patients. This could be related to lack of training, poor knowledge on the disease and lack of lab equipment in the African continent [1]. In another view, sometimes, treatment is proposed empirically based on clinical and radiological arguments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation